Masjid sebagai Pusat Komunikasi Dakwah dan Pembangunan Sosial di Era Masyarakat Digital - Abdul Aziz (Pawarta: Journal of Communication and Da'wah, 2026)
In the digital era, mosques serve not only as places of worship but also as centers for da'wah communication and social development. Advances in information technology have transformed patterns of community interaction, including the dissemination of religious values and social activities. Today, mosques face both challenges and opportunities in utilizing digital media to strengthen their strategic role within an increasingly connected society. The aim of this study is to analyze the role of mosques as centers of da'wah communication and social development in the digital era, as well as to identify optimal strategies for enhancing mosque functions in response to social and technological changes. The research employs a qualitative approach, using case studies of several mosques in major cities that actively utilize digital media. Research samples were selected purposively, and data were collected through in-depth interviews, observations, and analysis of digital documents related to mosque activities. The results show that mosques that adapt to digital technology are able to increase the reach of da'wah and the effectiveness of social programs. The use of social media and digital applications strengthens communication between mosque administrators and congregants, as well as encourages active community participation in religious and social activities. Mosques play a vital role in fostering da'wah and social communication in the digital era, with technology utilization serving as a key strategy to expand influence and strengthen community solidarity.